Evaluating the Friction Characteristics of Pavement Surface for Major Arterial Road - Mohammad, Diana Jumah; Ismael, Mohammed Qadir (Salehan Institute of Higher Education, 2021)
The performance of the pavement in terms of vehicle safety and tire wear is affected by the friction behavior of the pavement. To highlight the main characteristics that affect the production of better friction resistance of the pavement surface in this work. The micro-texture and macro-texture of the asphalt surface of Baghdad Airport highway were studied using two methods: (sand patch method and the British pendulum test). The sand patch was examined by drawing sand grains of a specific volume, while the micro-texture was analyzed using a BPT under dry and wet surface conditions. All data obtained from the two examinations were analyzed and modelled statistically using SPSS 25 software. Results show that skid resistance of pavement surface increase with the increase of MTD, this increase may be due to the increase of coarse aggregate which lead to increase the roughness of the pavement surface, this increase ranged between (96 - 91%). MTD decreases with the increase of traffic flow due to the friction between the road surface and the vehicle tires leading to increase of smoothness of the road surface. This is mean that MTD is highly affected by the traffic flow and this effectiveness ranged between (84-97%). Skid resistance also is highly affected by the traffic flow with an effectiveness ranged between (81-94%) for both pavement conditions. According to the regression analysis for friction and other parameters, it can be concluded that surface friction values are highly affected by cumulative traffic (asphalt mix deterioration) over time.Â Doi: 10.28991/cej-2021-03091775 Full Text: PDF